2015
DOI: 10.1093/nar/gkv228
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to high-yield biosynthesis of chimeric RNAs bearing various types of functional small RNAs for broad applications

Abstract: RNA research and therapy relies primarily on synthetic RNAs. We employed recombinant RNA technology toward large-scale production of pre-miRNA agents in bacteria, but found the majority of target RNAs were not or negligibly expressed. We thus developed a novel strategy to achieve consistent high-yield biosynthesis of chimeric RNAs carrying various small RNAs (e.g. miRNAs, siRNAs and RNA aptamers), which was based upon an optimal noncoding RNA scaffold (OnRS) derived from tRNA fusion pre-miR-34a (tRNA/mir-34a).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
169
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(172 citation statements)
references
References 40 publications
3
169
0
Order By: Relevance
“…Consequently, mature miR-1291 levels were increased by 2 orders of magnitude, indicating a successful processing of tRNA/mir-1291 to mature miR-1291. It is noteworthy that all recombinant ncRNAs, such as tRNA/mir-27 , tRNA/ mir-1291 (this study), and tRNA/mir-34a (Chen et al, 2015) (unpublished data), showed favorable cellular stability and selective generation of target mature miRNAs, suggesting that tRNA carrier also offers a "stealth delivery" of target miRNAs into human cells beyond the production of chimeric ncRNAs in bacteria. Nevertheless, further studies are warranted to define the specific RNases involved in the processing of recombinant ncRNAs in human cells.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Consequently, mature miR-1291 levels were increased by 2 orders of magnitude, indicating a successful processing of tRNA/mir-1291 to mature miR-1291. It is noteworthy that all recombinant ncRNAs, such as tRNA/mir-27 , tRNA/ mir-1291 (this study), and tRNA/mir-34a (Chen et al, 2015) (unpublished data), showed favorable cellular stability and selective generation of target mature miRNAs, suggesting that tRNA carrier also offers a "stealth delivery" of target miRNAs into human cells beyond the production of chimeric ncRNAs in bacteria. Nevertheless, further studies are warranted to define the specific RNases involved in the processing of recombinant ncRNAs in human cells.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, miR-1291 has been revealed to act as a tumor suppressor in various human carcinoma cell lines by our studies Bi et al, 2014) (unpublished data) as well as others (Hidaka et al, 2012;Yamasaki et al, 2013). Motivated by the idea of producing natural miRNA agents to perform miRNA actions, we made large efforts to biosynthesize pre-miR-1291 agents using the tRNA scaffold to examine miR-1291 biologic functions and therapeutic implications in vitro and in vivo Chen et al, 2015). The success and efficiency in producing recombinant RNAs relies on the structure and metabolic stability of target RNA in the organism.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations